GEDJETS INPACT ON CHILDRENS EDUCATION - Syarif Hidayat (Proceeding International Seminar of Islamic Studies, 2022)
the research is motivated by problems in the misuse of gedjet.gedjet is avery dangerous inpact for minors. Who are also teachers and parents in childrens education. As for this study using qualitative data analysis techniques. By conducting special observation and studies.as for the location of the problem, yes, namely the lack of attention from parents to give gedjet to minors. To solve this problem, teachers and parents must always control the child to give directions that the danger is gedjet. aims to overcome and fine out the effects that will occur whwnoneuses a gedjet which is misuse in the use of a gedjet.fromdhis research it is very desirable that there will be a change to studensts that the misuse of gedjet is very dangerous, especially to dhe point of damaging moral behavior, which is even worse for religious development. As for the medhods listed are to invite children, But the most importan and the most importan is dhe role of parents who must be able to become the main guiding role model for children.Kaiwords: Avoidance, the danger of getjet, in childrens education